Biobased polyelectrolyte multilayer-coated hollow mesoporous silica as a green flame retardant for epoxy resin - Jiang, Shu-Dong; Tang, Gang; Chen, Junmin; Huang, Zheng-Qi; Hu, Yuan (Journal of hazardous materials, 2018)
•A green flame retardant (HM–SiO2@CS@PCL) was successfully synthesized through layer-by-layer assembly.•The integrated effect of HM–SiO2@CS@PCL endows epoxy resin with excellent flame retardancy.•The incorporation of HM–SiO2@CS@PCL can recycle epoxy resin into high value-added hollow carbon spheres. Here, we describe a multifunctional biobased polyelectrolyte multilayer-coated hollow mesoporous silica (HM-SiO2@CS@PCL) as a green flame retardant through layer-by-layer assembly using hollow mesoporous silica (HM-SiO2), chitosan (CS) and phosphorylated cellulose (PCL). The electrostatic interactions deposited the CS/PCL coating on the surface of HM-SiO2. Subsequently, this multifunctional flame retardant was used to enhance thermal properties and flame retardancy of epoxy resin. The addition of HM-SiO2@CS@PCL to the epoxy resin thermally destabilized the epoxy resin composite, but generated a higher char yield. Furthermore, HM-SiO2 played a critical role and generated synergies with CS and PCL to improve fire safety of the epoxy resin due to the multiple flame retardancy elements (P, N and Si). This multi-element, synergistic, flame-retardant system resulted in a remarkable reduction (51%) of peak heat release rate and a considerable removal of flammable decomposed products. Additionally, the incorporation of HM-SiO2@CS@PCL can sustainably recycle the epoxy resin into high value-added hollow carbon spheres during combustion. Therefore, the HM-SiO2@CS@PCL system provides a practical possibility for preparing recyclable polymer materials with multi-functions and high performances.